The drug sensitivity and transmission dynamics of human malaria on Nias Island, North Sumatra, Indonesia. - Fryauff, D; Leksana, B; Masbar, S; Wiady, I; Sismadi, P; Susanti, A; Nagesha, H; Syafruddin; Atmosoedjono, S; Bangs, M; Baird, J (2002)
Nias Island, off the north-western coast of Sumatra, Indonesia, was one of the first locations in which chloroquine-resistant Plasmodium vivax malaria was reported. This resistance is of particular concern because its ancient megalithic culture and the outstanding surfing conditions make the island a popular tourist destination. International travel to and from the island could rapidly spread chloroquine-resistant strains of P. vivax across the planet. The threat posed by such strains, locally and internationally, has led to the routine and periodic re-assessment of the efficacy of antimalarial drugs and transmission potential on the island. Active case detection identified malaria in 124 (17%) of 710 local residents whereas passive case detection, at the central health clinic, confirmed malaria in 77 (44%) of 173 cases of presumed 'clinical malaria'. Informed consenting volunteers who had malarial parasitaemias were treated, according to the Indonesian Ministry of Health's recommendations, with sulfadoxine-pyrimethamine (SP) on day 0 (for P. falciparum) or with chloroquine (CQ) on days 0, 1 and 2 (for P. vivax). Each volunteer was then monitored for clinical and parasite response until day 28. Recurrent parasitaemia by day 28 treatment was seen in 29 (83%) of the 35 P. falciparum cases given SP (14, 11 and four cases showing RI, RII and RIII resistance, respectively). Recurrent parasitaemia was also observed, between day 11 and day 21, in six (21%) of the 28 P. vivax cases given CQ. Although the results of quantitative analysis confirmed only low prevalences of CQ-resistant P. vivax malaria, the prevalence of SP resistance among the P. falciparum cases was among the highest seen in Indonesia. When the parasites present in the volunteers with P. falciparum infections were genotyped, mutations associated with pyrimethamine resistance were found at high frequency in the dhfr gene but there was no evidence of selection for sulfadoxine resistance in the dhps gene. Night-biting mosquitoes were surveyed by human landing collections and tested for sporozoite infection. Among the five species of human-biting anophelines collected, Anopheles sundaicus was dominant (68%) and the only species found to be infective--two (1.2%) of 167 females being found carrying P. vivax sporozoites. The risk of malarial infection for humans on Nias was considered high because of the abundance of asymptomatic carriers, the reduced effectiveness of the available antimalarial drugs, and the biting and infection 'rates' of the local An. sundaicus.